Neurological Practice in the Time of War: Perspectives and Experiences from Ukraine - Flomin, Yuriy; Dubenko, Andriy; Dubenko, Olga; Sokolova, Larysa; Slobodin, Tatyana; Shepotinnyk, Yevhen; Guliaieva, Maryna; Pezzella, Francesca Romana (Seminars in Neurology, 2024)
The full-scale Russian invasion of Ukraine has significantly impacted the country's healthcare system. Insufficient infrastructure, destruction of medical facilities, and barriers to prevention and treatment efforts hinder the provision of timely, high-quality care to our patients. We aim to describe the impact of the war on neurological care across Ukraine. In this article, leading national experts in stroke, epilepsy, multiple sclerosis, and movement disorders describe their personal experience and efforts in organizing and providing care since the war started in February 2022. A neurologist who cared for patients in Mariupol recounts the first weeks of the war when the city was under constant attacks. An international stroke expert describes the role of Task Force for Ukraine, a European Stroke Organization initiative to support the Ukrainian stroke community. We discuss a series of critical challenges facing Ukraine's neurologists, patients, and healthcare delivery system, including shortages of personnel and medical supplies, disrupted logistics, and lack of funding. In addition, we highlight various interventions and strategies aimed at counteracting these challenges, including international support, collaborations within Ukraine, and initiatives enhancing the resilience of the Ukrainian neurology community. As the war is ongoing, this article emphasizes the pressing need for continuous support and investment in the Ukrainian healthcare system to preserve guaranteed access to high-quality healthcare for the Ukrainian people during the war and in its aftermath. Insights from the essays can inform the development and implementation of effective strategies and interventions tailored to such extraordinary circumstances.
Keywords: Ukraine; war; armed conflicts; neurology; stroke; epilepsy; multiple sclerosis; movement disorders; neurological practice